Effect on Lung Structure, Inflammatory and Nutritional Status of COPD Patients with Fibrotic and Proliferative Tuberculosis Changes in Chest Imaging - Ghimire, Hridaya Bibhu; Li, Jian Guo; Yong-Xun, Zhuan Sun (Journal of Nobel Medical College, 2014)
Background and objectives Tuberculosis and COPD are common diseases in developing countries, sharing risk factors like smoking and low socio-economic status but little is known about the specific relationship between tuberculosis and COPD. Methods Retrospective analysis was done. All COPD patients with either fibrotic and proliferative tubercular changes in chest imaging or none of the features of tuberculosis (in chest imaging, sputum test, skin test or history) admitted in Sun Yat- Sen Memorial Hospital, China from the year 2007 to 2010 were taken for the study. Clinical features along with post– bronchodilator FEV1/FVC<70% were used as a basis for the diagnosis of COPD. Results Among 84 COPD patients with fibrotic and proliferative tuberculosis changes in chest imaging, 20 of them had bullae or blebs in their radiologic examination whereas only 11 of 105 non-tuberculosis COPD cases had those features, Pearson Chi Square value=6.05, p=0.014. COPD patients with fibrotic and proliferative tuberculosis changes had lower blood iron, transferrin, albumin but higher high sensitive CRP (hsCRP) (p=0.010, 0.003, 0.010 and 0.032 respectively) compared to non-tuberculosis COPD cases. Conclusions Fibrotic and proliferative tuberculosis changes in COPD results in greater inflammation and damage to lung tissue (determined by increase bullae formation, higher hsCRP level) with decrease in basic nutritional elements. DOI: http://dx.doi.org/10.3126/jonmc.v3i1.10053 Journal of Nobel Medical College Vol.3(1) 2014; 40-44